SIX SIGMA LEVERAGE : A SME PERSPECTIVE - LOH, KONG NGEE (2010)
Having arisen in large Multinational Corporations (MNCs), Six Sigma is recognized as one of the most comprehensive approaches for company developments and performance improvements. However, it appears that majority of Small and Medium Enterprises (SMEs) do not leverage Six Sigma for the mentioned benefits. This paper explores why SMEs should leverage Six Sigma in their Business Excellence model to improve the company and financial performances, and how SMEs in Singapore could overcome some of the common difficulties to implementation. A combination of literature review based on the experiences of both academics and practitioners on Six Sigma, and empirical research conducted on SMEs in Singapore will be employed in the study. This paper reports the first study on the Six Sigma implementation in Singapore SMEs. The paper will yield values to academics, consultants, researchers, and more importantly to SMEs in successful deployment of Six Sigma.